Short communication impact of environmental factors on the larval population of bagworm, Metisa plana WALKER (LEPIDOPTERA: PSYCHIDAE) in oil palm smallholdings - Nur Robaatul Adhawiyah Mohd Ali Napiah,; Noorhazwani Kamarudin,; Shamsilawani Ahmad Baker,; Nurhafizhoh Zainuddin,; Mohd Fahmi Keni,; Mohamed Mazmira Mohd Masri, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Infestations and outbreaks of bagworms, Metisa plana Walker (Lepidoptera:Psychidae) have been reported primarily in Peninsular Malaysia for many years. Bagworm infestation is a significant problem primarily due to the mismanagement and lack of proper monitoring in the field, which later affected the yield and profit loss, especially among smallholders. Understanding the impact of environmental conditions on bagworms may assist in a more proper pest control strategy. Changes in environmental conditions have the potential to interrupt the bagworm's life cycle. This study investigated the effects of temperature, humidity, and rainfall on the bagworm population in selected smallholding oil planted areas in Johor. Anemometer was used to collect the data of temperature and humidity while the collection of rainfall was taken from Meteorology Station. The results showed that temperature (r= 0.211) and rainfall (r= 0.108) have minimal effects on the bagworm population, recording positive relationships with Metisa plana. Relative humidity (r= -0.203), however, showed a negative correlation with M. plana. The findings suggested that temperature and rainfall may affect bagworm populations, but a long-term study is required to comprehend this impact fully. An improve scientific approach should be used in future research along with suitable Integrated Environmental Pest Management (IEPM) techniques, monitoring of the climate and pests, and the use of modelling tools as mitigation strategies to determine the effects of environmental factors in bagworms.